New proteasome inhibitors in the management of multiple myeloma - S. V. Semochkin (Онкогематология)
The landscape of multiple myeloma treatment transformed at the last 15 years by the introduction of novel agents (bortezomib, lenalidomide) and wide application of autologous hematopoietic stem cell transplantation, which have prolonged the survival of multiple myeloma patients. Despite the fact that multiple myeloma remains an incurable disease due to the new options, the median overall survival of patients with multiple myeloma in Russia in 2006–2016 was about 55–68 months. Drug resistance and clonal evolution remain a problem. The novel proteasome inhibitors (carfilzomib, ixazomib) differ in chemical structure and pharmacological characteristics. Thereby the next-generation proteasome inhibitor (IPs)-based regimens (KRd (carfilzomib, lenalidomide, dexamethasone), IRd (ixazomib, lenalidomide, dexamethasone), and Kd (carfilzomib, dexamethasone)) are emerging as new standards for the treatment of patients with relapsed and/or refractory multiple myeloma. In a randomized trial phase 3 ENDEAVOR, carfilzomib demonstrated improved survival in direct comparison to bortezomib. The dose-dependent activity of carfilzomib demonstrated in the study of A.R.R.O.W. Аctivity of ixazomib is comparable to that of bortezomib, the oral method of administration and the absence of neurological toxicity, allow for long-term control of the disease. The new PIs are an important advance in relapsed and/or refractory multiple myeloma treatment, increasing survival, response rate and quality of life, even in subgroups of patients with poor prognosis. This review summarizes the main pharmacological properties, mechanisms of action and clinical outcomes of major clinical studies with these agents. A separate issue discusses the problem of overcoming new proteasome inhibitors of drug resistance to bortezomib.